2001
DOI: 10.1161/hh1201.091794
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Pathway Is Required for Endothelin-1–Mediated Protection Against Oxidant Stress–Induced Apoptosis in Cardiac Myocytes

Abstract: Abstract-Endothelin-1 (ET-1) acts not only as a growth-promoting peptide but also as a potent survival factor against myocardial cell apoptosis. However, the signaling pathways leading to myocardial cell protection by ET-1 are poorly understood. Using a culture system of primary cardiac myocytes derived from neonatal rats, we show in the present study that ET-1 almost completely blocked the hydrogen peroxide-induced increase in the percentage of TdT-mediated dUTP-biotin nick-end labeling-positive myocytes. Apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
92
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 33 publications
11
92
0
Order By: Relevance
“…23 In cardiac myocytes, ET-1 prevents oxidative stress-and ␤-adrenergic agonist-induced apoptosis. 24,25 In the present study, we demonstrate that ET-1 prevents apoptosis induced by serum deprivation in cultured cardiac myocytes and investigate the signaling pathways that mediate the antiapoptotic effect of ET-1.…”
mentioning
confidence: 83%
“…23 In cardiac myocytes, ET-1 prevents oxidative stress-and ␤-adrenergic agonist-induced apoptosis. 24,25 In the present study, we demonstrate that ET-1 prevents apoptosis induced by serum deprivation in cultured cardiac myocytes and investigate the signaling pathways that mediate the antiapoptotic effect of ET-1.…”
mentioning
confidence: 83%
“…The cardiac myocytes were grown on flask-style chambers with glass slides (Nalgen Nunc, Naperville, IL) and then stimulated with saline or 1.0 ϫ 10 Ϫ5 M of PE in serum-free medium for 48 h. The cells were then fixed with 3% formaldehyde in phosphate-buffered saline for 15 min at room temperature. Immunocytochemical staining for ␤-MHC was performed using the indirect immunoperoxidase or immunofluorescense method as previously described (27). As the primary antibody we used anti-␤-MHC polyclonal antibody (NovoCastra Laboratories Ltd., Newcastle, UK) at a dilution of 1:50.…”
Section: Methodsmentioning
confidence: 99%
“…In adult cardiac myocytes, Kakita, et al reported that the calcineurin/NFAT/GATA4 pathway is required for ET-1-mediated protection against cardiac myocyte apoptosis. 19) Cardiac-specific deletion of GATA4 induces apoptosis by alteration of the gene expression implicated in cellular apoptosis after pressureoverload. 20) The overexpression of GATA4 has been shown to prevent cardiac myocyte apoptosis induced by anthracyclines Vol 57 No 6 GATA4 MODIFICATIONS IN CARDIOMYOCYTE HYPERTROPHY such as daunorubicin and doxorubicin.…”
Section: Gata4mentioning
confidence: 99%